On a certain nonlocal problem for a heat equation - Danilkina, Olga (Global Journal of Mathematical Analysis, 2014)
The aim of this paper is to study the nonlocal problem with the integral condition of the first kind for the heat equation. We prove existense and uniqueness of a generalized solution for this problem. The proof is based on the obtained apriory estimate and Galerkin method. Keywords: Energy Inequality, Galerkin Method, Heat Equation, Nonlocal.